Analysis of Digital Marketing Strategies in Increasing Sales of Singgasana Cafe and Resto in Tanjung Bumi District Bangkalan Regency - Sulis, Yuliana Dewi; Anshori, Mochammad Isa; Andriani, Nurita (Lembaga Riset dan Inovasi Al-Matani, 2024)
Digital marketing strategy that can increase sales of Singgasana Cafe and Resto in Tanjung Bumi District , Bangkalan Regency. This research is based on This is due to the increasingly competitive culinary business context, where the existence of digital marketing has become important to attract customers and expand market share. Singgasana Cafe and Resto, which was founded in 2015, has become a popular destination with a charming beach panorama. The aim of this research is to understand the digital marketing practices implemented by Singgasana Cafe and Resto and analyze their impact on increasing sales. The research method used is a qualitative method with a Systematic Literature Review (SLR) approach and direct interviews with the Cafe Owner, namely Mr. Mohammad Sahri SH, MH,. and mrs. Nia manager . SLR is used to identify trends, best practices, and current research. related to digital marketing strategies in the culinary industry. Interviews with owners and managers were conducted to gain in-depth insight into the implementation of digital marketing strategies at Singgasana Cafe and Resto. The research results show that Cafe and Resto Singgasana has succeeded in integrating digital marketing strategies well, including the use of social media, personalization of services, and use of Point-of-Sale (POS) technology. Implementation of this strategy has a positive impact on sales, increases customer engagement, and strengthens the brand image of Cafe and Resto Singgasana.